Oxide formation on titanium alloys in primary water of nuclear pressurised water reactor. (15th April 2019) - Bignon, Quentin; Martin, Frantz; Auzoux, Quentin; Miserque, Frédéric; Tabarant, Michel; Latu-Romain, Laurence; Wouters, Yves
Highlights: The oxide layer formed is made of a dense oxide layer covered by crystallites. The continuous dense TiO2 scale is made of rutile for Ti CP and anatase for α/β alloys. All alloys are covered by small TiO2 anatase and large FeTiO3 ilmenite crystallites. The dissolution of TiO2 dense scale plays a key role in the corrosion mechanisms. Oxygen vacancy is the main point defect responsible for the growth of the dense TiO2 layer. Abstract: Three titanium alloys were exposed to primary water at 300 °C. Oxides of the three alloys consisted of a dense layer and surface crystallites. The dense oxide layer of Ti CP was made of TiO2 rutile whereas it was made of TiO2 anatase for both Ti 64 and Ti10-2-3. Surface crystallites of the three alloys were composed of TiO2 anatase and FeTiO3 ilmenite. Oxide dissolution and precipitation phenomenon were found to play a key role in the corrosion mechanisms. Oxygen vacancies were identified as the main point defect responsible for the growth of the dense oxide layer.